2011
DOI: 10.1097/mbp.0b013e32834af7ba
|View full text |Cite
|
Sign up to set email alerts
|

The relation between health literacy, hypertension knowledge, and blood pressure among middle-aged Japanese adults

Abstract: Lower HL and HK were associated with a poor health status and BP level in middle-aged participants. Further research is needed to examine the role of health management in improving outcomes and to address disparities between individuals with higher and lower HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
2
23
2
8
Order By: Relevance
“…The results of path model revealed that health skills, health concept, general knowledge and knowledge of infectious disease had direct effects on health behaviors, which were consistent with findings from previous studies [3], . One study from Japan indicated that individuals with less health skills had a significantly higher rate of smoking, and were more likely to have a history of hypertension [3].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of path model revealed that health skills, health concept, general knowledge and knowledge of infectious disease had direct effects on health behaviors, which were consistent with findings from previous studies [3], . One study from Japan indicated that individuals with less health skills had a significantly higher rate of smoking, and were more likely to have a history of hypertension [3].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies [3], [6], [10], [15][21] have given the relationship between socio-demographic characteristics, health knowledge, health skills, health behaviors and health outcomes, they are all theoretical explanations. Few studies have tried to validate them through the use of statistical modeling.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the World Health Organization (WHO) definition, a model of HL has been proposed that includes three levels, and assumes both individual and population benefits at each level: functional, communicative, and critical literacy. 9 Individuals with adequate HL are considered likely to adopt healthy lifestyles, 10,11 and a brief questionnaire was developed to easily assess HL. 11,12 However, only a few studies have estimated the association between HL and healthy lifestyle characteristics among Japanese people, [11][12][13] and studies that examine the association among patients with lifestyle related disorders are especially limited.…”
Section: Introductionmentioning
confidence: 99%
“…2 Specifically, those with limited HL often lack medical-related knowledge, 3 use fewer preventive services, 4 are more likely to be hospitalized, 5 and experience worse health-related outcomes. 6 Numeracy is a key, but largely understudied, component of HL.…”
mentioning
confidence: 99%